Reduced susceptibility to eccentric exercise-induced muscle damage in resistance-trained men is not linked to resistance training-related neural adaptations - X Ye; TW Beck; NP Wages (Termedia Publishing House, 2015)
The purpose of this study was to examine the acute effects of maximal concentric vs. eccentric exercise on the isometric strength of the elbow flexor, as well as the biceps brachii muscle electromyographic (EMG) responses in resistance-trained (RT) vs. untrained (UT) men. Thirteen RT men (age: 24 ± 4 years; height: 180.2 ± 7.7 cm; body weight: 92.2 ± 16.9 kg) and twelve UT men (age: 23 ± 4 years; height: 179.2 ± 5.0 cm; body weight: 81.5 ± 8.6 kg) performed six sets of ten maximal concentric isokinetic (CON) or eccentric isokinetic (ECC) elbow flexion exercise in two separate visits. Before and after the exercise interventions, maximal voluntary contractions (MVCs) were performed for testing isometric strength. In addition, bipolar surface EMG signals were detected from the biceps brachii muscle during the strength testing. Both CON and ECC caused isometric strength to decrease, regardless of the training status. However, ECC caused greater isometric strength decline than CON did for the UT group (p = 0.006), but not for the RT group. Both EMG amplitude and mean frequency significantly decreased and increased, respectively, regardless of the training status and exercise intervention. Resistance-trained men are less susceptible to eccentric exercise-induced muscle damage, but this advantage is not likely linked to the chronic resistance training-induced neural adaptations.